Batimetria e estudo de parâmetros morfométricos do reservatório da floresta estadual “edmundo navarro de andrade” (FEENA) RIO CLARO/SP - Cigagna, Cristiano [UNESP]; Bonotto, Daniel Marcos [UNESP]; Sturaro, José Ricardo [UNESP] (My University, 2014)
This study describes the bathymetric survey and characterization of the main morphometric parameters of the reservoir located in the State Forest Edmundo Navarro de Andrade. 271 reservoir depth values were measured along 10 transects. These data were used to estimate, by ordinary kriging, the bathymetric maps that were the basis for the calculation of the main morphometric parameters of the reservoir. The results present the atual condiction of siltation in the reservoir, and the possible influence of morphometry in your current high trophic level. The knowledge and the proper interpretation of the overall data submitted are of great value for planning actions that seek recovery of the ecological quality of the reservoir. In this context, geostatistics has been the main tool used for a surface adjustement according to techniques of robust estimate.
Bathymetry and study parameters of reservoir morphometric state forest “edmundo navarro de andrade” (FEENA) rio claro / sp
Keywords: Geostatistics; Kriging; Limnology; Morphometry